The influence of the unloading mode of asphalt concrete mixing plant hot bin on the homogeneity of screened fractions - SiviIevičius, Henrikas (Transport, 2005)
The analysis of hot asphalt concrete mixture production in asphalt concrete mixing plants of intermittent operation according to the traditional technology scheme is presented. The segregation degree of hot mineral materials fractions of 0–5 mm and 5–15 mm sieved in hot bins and the influence of their screening mode on the homogeneity of the flow running to the measuring hopper were identified during the experimental tests carried out in two asphalt concrete mixing plants. To evaluate the degree of segregation and kinetics according to three different methodologies 214 separate samples of hot fractions grouped into three series A, B, C were taken. Statistical characteristics of each series samples grading and coarseness modulus (fraction of 0–5 mm) as well as arbitrary coarseness modulus (fraction of 5–15 mm) were identified. The data analysis proved that the degree of segregation of hot materials sieved in the bin sections is high and the homogeneity of their flows decreases when the range and frequency of quantity fluctuation increases.First Published Online: 27 Oct 2010